The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1097/ta.0b013e318265ce1f
|View full text |Cite
|
Sign up to set email alerts
|

Restrictive fluid resuscitation in combination with damage control resuscitation

Abstract: Therapeutic study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
59
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 26 publications
1
59
0
4
Order By: Relevance
“…This includes both positive fluid balance per day over an extended period of time during the hospitalization, as well as high ''throughput'' of IV fluids in the setting of an even fluid balance. It is now well documented that both management strategies are harmful in patients with sepsis, ARDS, after trauma or during the perioperative period [3][4][5][6][7][8][9]. However, the exact mechanism remains unclear.…”
mentioning
confidence: 99%
“…This includes both positive fluid balance per day over an extended period of time during the hospitalization, as well as high ''throughput'' of IV fluids in the setting of an even fluid balance. It is now well documented that both management strategies are harmful in patients with sepsis, ARDS, after trauma or during the perioperative period [3][4][5][6][7][8][9]. However, the exact mechanism remains unclear.…”
mentioning
confidence: 99%
“…After this report, several randomized or retrospective studies concerning balanced resuscitation were reported; however, the benefit to mortality varied among the studies [28][29][30][31]. Turner et al randomized more than 1000 patients to immediate or delayed resuscitation in the prehospital setting but showed no beneficial effects on mortality [28].…”
Section: Balanced Resuscitationmentioning
confidence: 99%
“…Сьогодні вона перебуває в стадії актив-ної розробки і не має чітко доведених доз, обсягу, складу препаратів, проте її переваги вже не викли-кають сумнівів [2]. Так, наприклад, Duke et al (2012) …”
unclassified
“…Сьогодні вона перебуває в стадії актив-ної розробки і не має чітко доведених доз, обсягу, складу препаратів, проте її переваги вже не викли-кають сумнівів [2]. Так, наприклад, Duke et al (2012) показали значне зниження частоти несприятливих наслідків у травмованих пацієнтів (n = 307), у яких застосовували рестриктивну стратегію ІТ, в порів-нянні з групою ліберальної стратегії. Інтраоперацій-на смертність складала 9 і 32%, тривалість госпіта-лізації -13 і 18 діб, смертність у відділеннях інтен-сивної терапії -5 і 12% відповідно [10].…”
unclassified
See 1 more Smart Citation